Artificial intelligence in recruitment: just because it´s biased, does it mean it´s bad? - Beneduce, Giusy (2021)
In recent years, artificial intelligence technologies have seen a major diffusion. Despite the numerous benefits, some concerns arise around the possibility that artificial intelligence may inherit human bias. This paper addresses to what extent artificialintelligence bias is a blocker to the implementation of those technologies in recruitment. The research was developed focusing on gender bias and data was gathered through a survey-based questionnaire. Data shows that recruiters consider artificial intelligence an opportunity to improve the recruitment process, however, bias does represent a disincentiveto the implementation of those technologies.